2019
DOI: 10.20517/2394-4722.2018.81
|View full text |Cite
|
Sign up to set email alerts
|

The molecular interaction of ADAMTS-1 and fibulin-1 and its potential contribution to breast cancer biology

Abstract: Aim: Fibulins and ADAMTSs are two families of extracellular matrix proteins implicated in key functional and pathological processes. The fact that the fibulin-1 and ADAMTS-1 proteins interact raises new questions about the roles of these extracellular matrix proteins in modulating tumor progression. Herein, we described the functional implications of the interaction between fibulin-1 and ADAMTS-1 on the behavior of breast cancer cell lines. Methods: Fibulin-1 and ADAMTS-1 were exogenously expressed in MCF-7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, in patients with Philadelphia-negative chronic myeloproliferative neoplasms (MPNs), a significantly increased expression of fibulin-1 is observed, which in turn might enhance the capacity of TGF- β, as TGF- β anticipates various regulatory functions shown by fibulins and promotes cancer progression [ 95 ]. In contrast, the interaction of fibulin-1 with ADAMTS-1 in breast cancer cell lines induces an anticancer effect [ 96 ]. Another study on ovarian cancer reported an increased expression of the fibulin-1C splice variant, concluding that fibulin-1C promotes the progression of ovarian cancer [ 97 ].…”
Section: Role Of Fibulins During Cancer Progressionmentioning
confidence: 99%
“…Additionally, in patients with Philadelphia-negative chronic myeloproliferative neoplasms (MPNs), a significantly increased expression of fibulin-1 is observed, which in turn might enhance the capacity of TGF- β, as TGF- β anticipates various regulatory functions shown by fibulins and promotes cancer progression [ 95 ]. In contrast, the interaction of fibulin-1 with ADAMTS-1 in breast cancer cell lines induces an anticancer effect [ 96 ]. Another study on ovarian cancer reported an increased expression of the fibulin-1C splice variant, concluding that fibulin-1C promotes the progression of ovarian cancer [ 97 ].…”
Section: Role Of Fibulins During Cancer Progressionmentioning
confidence: 99%
“…However, fibulin-1 expression in the stroma is associated with increased malignancy in ovarian and breast cancers (32). Thus, the ambiguous function associated with fibulin-1 in tumor-related processes has several possible explanations: posttranslational modifications, such as the proteolytic processes affecting fibulin-1 in mammary tumors; alternative splicing, which generates the different forms of fibulin-1; interaction of fibulin-1 with different components of the ECM; or even the areas where fibulin-1 is expressed [stromal vs. tumor cells; (22, 3335)].…”
Section: Fibulin-1 and Its Associations With Adamtssmentioning
confidence: 99%
“…In a recent study, the interaction between fibulin-1 and ADAMTS-1 was associated with antitumor effects in breast cancer cell lines (35). In fact, over-expression of exogenous ADAMTS-1 and fibulin-1 resulted in a reduction in the invasive and migratory phenotypes of these cell lines.…”
Section: Fibulin-1 and Its Associations With Adamtssmentioning
confidence: 99%
“…One study shows that overexpression of FBLN-1 in breast cancer cell lines promotes resistance to doxorubicin [ 36 ], whereas another study reports that inhibition of FBLN-1 in cancer cell lines increases the sensitivity to the same drug [ 37 ]. It is also reported that FBLN-1 interacts with the protumor ADAMTS-1 to block the activity of the latter in promoting the proliferation and migration of breast cancer cells [ 38 ]. Because of the scarcity of literature on the role of the ectopic FBLN-1 protein in the growth suppression of breast cancer cells, this subject matter may open up a new direction for cancer research.…”
Section: Discussionmentioning
confidence: 99%